Vacutainer serum separator sebagai alternatif tabung penampung darah pada pemeriksaan kadar ureum - Budi Setiawan; Ulfah Restu Nugraheni; Muji Rahayu (Universitas Muhammadiyah Surabaya, 2021)
ABSTRACT Serum using is preferred for urea level because it does not use anticoagulants which can interfere with activity and reaction to the results. The tubes that are widely used to collect blood into serum are vacutainer serum separator and vacutainer plain.This researche aims to determine the degree of agreement s between vacutainer serum separator and vacutainer plain usage on serum urea level result.This research was cross sectional design and hold on October 2020 with subject were taken from thirty blood samples of health analyst students which taken randomly and had no history of disease or kidney function disorder. Each student was taken 6 ml of blood drawn using a venoject with each vacutainer containing 3 ml, so we had 60 data. The data were analyzed by descriptively and inferentially using the Interclass Correlation Coefficient (ICC) statistical test. From the descriptive analysis, the difference in mean levels was 0.35 mg/dL and the ICC statistical test resulted in a degree of agreement 0.745. The data were analyzed by descriptively and inferentially using the Interclass Correlation Coefficient (ICC) statistical test. From the descriptive analysis, the difference in mean levels was 0.35 mg/dL and the ICC statistical test resulted in a degree of agreement was 0.745. The calculation of the average working time between the vacutainer serum separator and the vacutainer plain was 4 minutes 38 seconds and 35 minutes 58 seconds. The analysis concluded that the vacutainer serum separator and the vacutainer plain could be used as an alternative of blood collecting tubes for urea level testing which proved to be no significant difference in the results from this research. Keywords : Urea level, Vacutainer Serum Separator, Vacutainer Plain